(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the consideration of "green" investment, which is gaining popularity among investors. The concept of responsible investment is revealed. The role of the COVID-19 pandemic in increasing the volume of ESG investments is considered. The key trends that will lead to the growth of assets invested in global ESG funds have been identified. The research is based on the methods of the dialectical method of scientific research, as well as logical methods, including analysis and synthesis.